12=4-3f+7

Simple and best practice solution for 12=4-3f+7 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 12=4-3f+7 equation:


Simplifying
12 = 4 + -3f + 7

Reorder the terms:
12 = 4 + 7 + -3f

Combine like terms: 4 + 7 = 11
12 = 11 + -3f

Solving
12 = 11 + -3f

Solving for variable 'f'.

Move all terms containing f to the left, all other terms to the right.

Add '3f' to each side of the equation.
12 + 3f = 11 + -3f + 3f

Combine like terms: -3f + 3f = 0
12 + 3f = 11 + 0
12 + 3f = 11

Add '-12' to each side of the equation.
12 + -12 + 3f = 11 + -12

Combine like terms: 12 + -12 = 0
0 + 3f = 11 + -12
3f = 11 + -12

Combine like terms: 11 + -12 = -1
3f = -1

Divide each side by '3'.
f = -0.3333333333

Simplifying
f = -0.3333333333

See similar equations:

| 2(7+n)=40 | | 3.7x-2.2=16.3 | | 1.62y=3.14(y-8.62) | | 5(2x-3)-6x=0.5(4x+10) | | 10m-50+20p=0 | | f(x)=x^2+4x-32 | | -7x+12=x-6 | | n+n+56=180 | | 3(5+n)=150 | | 2x+0=7 | | -5m-3=3+5m | | 2x-3.8+x=62 | | 8(4+n)=88 | | 3-bc=35 | | 5(3+n)=88 | | -2(p+1)+3=-15 | | 3x^2-6x+6x=0 | | 5(3+n)=90 | | g(0)=3(0)+2 | | (.0309+x)+27.1594637= | | 6x-3x+26=5(x+8) | | -2a+3=-2 | | 3ln(x)=15 | | 2*9-4+8*2=288 | | 5q=2p | | 10+3b-7b= | | m-2n=0 | | 3(4+n)=21 | | (4x+4)+(5x-3)+17=3x*4 | | x^2-5x+9x-12=180 | | 3(.3x+.1)+.2x= | | 3x^2+15x-108=0 |

Equations solver categories